A Strong AES Algorithm Using Hash Functions for Key Generation - Hoobi, Mays M.; Abdulmunem, Inas Ali (Iraqi Journal of Science, 2025)
The present world depends on communications. Increasing dependency on communications means the importance of information security is increasing than ever. Every user wants to keep the data secure by applying a strong data encryption concept. The strong data encryption can be satisfied by using a strong encryption algorithm and strong key. In this research, a method is proposed –Key Generation Method (KGM) to generate the strong unique keys for the cryptographic algorithm. This method includes using 22 different types of hash functions to generate 22 strong unique keys with different two lengths (128-bit and 256-bit), then applying these keys with the Advanced Encryption Standard (AES) algorithm. Analysis tools (entropy and autocorrelation) in addition to 5-NIST tests (frequency test, poker test, run test, long run test, and serial test) are used to evaluate the strength of AES ciphering. The results confirm that the proposed method for key generation can effectively satisfy the criteria of strong encryption against attackers.